Tadpoles of three western African frog genera: Astylosternus Werner, 1898, Nyctibates Boulenger, 1904, and Scotobleps Boulenger, 1900 (Amphibia, Anura, Arthroleptidae) - Frederic Griesbaum; Mareike Hirschfeld; Michael F. Barej; Andreas Schmitz; Mariam Rohrmoser; Matthias Dahmen; Fabian Mühlberger; H. Christoph Liedtke; Nono L. Gonwouo; Joseph Doumbia; Mark-Oliver Rödel (Zoosystematics and Evolution, 2019)
Herein, we describe the tadpoles of six Astylosternus species, A. fallax, A. cf. fallax, A. laurenti, A. montanus, A. perreti, A. ranoides, and Scotobleps gabonicus, and redescribe the tadpoles of A. batesi, A. diadematus, A. laticephalus, A. occidentalis, A. rheophilus, and Nyctibates corrugatus. All Astylosternus tadpoles are adapted to torrent currents and share a long, oval body, slightly flattened in lateral view, with very long muscular tails with narrow fins. The jaws are massive, serrated, and often show a tooth-like medial projection (fang) in the upper jaw. Body proportions of Astylosternus tadpoles are extremely similar. The best characters to distinguish species might be life coloration and potentially the shape of labial papillae. The tadpole of Scotobleps gabonicus is similar to Astylosternus and differs only slightly by a narrower body with a shorter and rounder head. The upper jaw of Scotobleps carries two or three lateral fangs instead of one medial one. The tadpole of Nyctibates corrugatus is easily distinguishable from the other two genera on the basis of their very long, eel-shaped body and tail and the bluish-black color.